Factors Determining Attempt-To-Quit Smoking Among Adult Current Smokers In Sarikei, Sarawak, Malaysia - Wong, Khung Ying; Md Mizanur, Rahman (Malaysian Journal of Public Health Medicine, 2017)
Achieving smoking cessation is an arduous process, where smokers try different methods or approaches to achieve cessation. Quit smoking attempts play an important role in smoking cessation.Thus, this study was conducted to determine the factors associated with attempt-to-quit smoking among the currentsmokers in Sarawak.This cross-sectional study was conducted among adult smokers in Sarikei, Sarawak by face-to-face interview using an adapted and validated questionnaire. Non-probability sampling method was used to select the study place. An adult smoker was selected systematically from each selected household. A total of 482 smoker households were identified with a response rate of 92.3%. Data was analysed using IBM SPSS Version 22.0. A p-value of <0.05 was considered statistically significant. The mean (SD) age of the smokers was 36.3(13.3) years. However, the mean (SD) age of smoking initiation was 18.5(4.8) years. Majority of the smokers were male (91.5%), with the male to female ratio being 1:0.1. Mean (SD) score on The Fagerström Test for Nicotine Dependence was 4.75(2.4), while motivation to quit smoking score was 3.04(1.0). Majority of the smokers (83.1%) hadever seen pictorial health warnings on cigarette packs. More than half of the smokers (54.8%) had ever tried to quit smoking. Binary logistic regression analysis revealed that marital status, religion, ethnicity, pictorial health warnings on cigarette packs and motivation to quit smoking appeared to be the significant predictors of attempt-to-quit smoking (p<0.05). Understanding the attempts to quit smoking will assist inclinical expectations. Thus, a smoking cessation programme should be designed in line with these factors, to aid quit smoking attempts.